1984
DOI: 10.1083/jcb.99.1.306
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of murine erythroleukemia cells results in the rapid repression of vimentin gene expression.

Abstract: We show that vimentin filaments are present in undifferentiated Friend murine erythroleukemia cells, but are lost progressively to undetectable levels by 96 h of dimethyl sulfoxide-mediated differentiation. The amount of newly synthesized cytoskeletal vimentin is decreased dramatically by 24 h of induction, and is paralleled by a rapid loss of vimentin mRNA (approximately 25-fold reduction at 96 h). Hence, disappearance of vimentin filaments in these cells appears to be regulated at the level of vimentin mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 59 publications
3
47
1
Order By: Relevance
“…On the contrary, vimentin RNA levels decreased when HL-60 cells were induced to differentiate with retinoic acid. Vimentin synthesis also decreases in the morphological differentiation of 3T3 adipocytes (53) and in differentiating erythroleukemia cells (39). This ambivalence of vimentin expression, by which its RNA levels increase both after stimulation of cellular proliferation and after induction of differentiation, should not be surprising.…”
Section: Discussionmentioning
confidence: 93%
“…On the contrary, vimentin RNA levels decreased when HL-60 cells were induced to differentiate with retinoic acid. Vimentin synthesis also decreases in the morphological differentiation of 3T3 adipocytes (53) and in differentiating erythroleukemia cells (39). This ambivalence of vimentin expression, by which its RNA levels increase both after stimulation of cellular proliferation and after induction of differentiation, should not be surprising.…”
Section: Discussionmentioning
confidence: 93%
“…Immunoelectron microscopic studies of avian erythrocytes suggested that vimentin is involved in anchoring the nucleus to the plasma membrane (Granger & Lazarides 1982). During erythroid differentiation of cultured erythroid precursor cells, vimentin expression is down-regulated, suggesting that removal of the vimentin network may be necessary for enucleation (Dellagi et al 1983;Ngai et al 1984;Sangiorgi et al 1990). Over-expression of vimentin in transgenic mice resulted in cataracts in the eye lens, possibly because the enucleation of lens cells during development was hampered (Capetanaki et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…[35S]methionine for 1 h as described previously (69). Equivalent amounts of protein-incorporated [35S] radioactivity in Triton X-100-insoluble residues (5, 62) from each sample were loaded on two-dimensional isoelectric focusing-SDSpolyacrylamide gels (70); gels were stained with Coomassie blue to visualize total protein and then impregnated with 2,5-diphenyloxazole for fluorography (7).…”
Section: Methodsmentioning
confidence: 99%
“…Equivalent amounts of protein-incorporated [35S] radioactivity in Triton X-100-insoluble residues (5, 62) from each sample were loaded on two-dimensional isoelectric focusing-SDSpolyacrylamide gels (70); gels were stained with Coomassie blue to visualize total protein and then impregnated with 2,5-diphenyloxazole for fluorography (7). Immunofluorescence microscopy with an anti-chicken vimentin antiserum (33) was performed exactly as described previously (69 57-nt extension products, corresponding to correctly initiated hamster vimentin mRNA, were quantitated by Cerenkov radiation determination of excised gel slices. Serial dilution of BHK-21 RNA (a source of high levels of hamster vimentin RNA) over a 20-fold range yielded a commensurate decrease in radioactive extension products (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation